DIGITAL HEALTH COMPETENCE AND HEALTHCARE SERVICE PERFORMANCE AMONG HEALTHCARE PROFESSIONALS IN SAUDI ARABIA - Ali Mohammed Albeah; Hafizah Che Hasan (PT. Jurnal Center Indonesia Publisher, 2026)
Digital transformation in healthcare services has significantly changed how healthcare professionals deliver clinical care, particularly in technology-based tertiary hospitals. Digital Health Competence (DHC) has become a crucial factor determining service effectiveness, clinical decision quality, and operational efficiency in modern healthcare organizations. This study aims to analyze the influence of digital health competence on healthcare service performance at King Abdullah Medical City (KAMC), Saudi Arabia, with work engagement as a mediating variable and organizational support as a moderating factor. This study employed a quantitative cross-sectional design. The sample consisted of 312 healthcare professionals at KAMC selected through stratified random sampling. Data were collected using a Likert-scale questionnaire ranging from 1 to 5 and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings revealed that digital health competence had a positive and significant effect on healthcare service performance (β = 0.412; p < 0.001). Digital competence also significantly influenced work engagement (β = 0.528; p < 0.001), while work engagement mediated the relationship between digital competence and healthcare service performance (β = 0.216; p < 0.001). Furthermore, organizational support strengthened the relationship between digital competence and work engagement. These findings indicate that digital competence not only improves service efficiency and quality but also functions as a psychological resource that enhances healthcare professionals’ motivation and dedication. Practically, the study provides important implications for hospitals in improving healthcare professionals’ digital competence through continuous training, the development of user-friendly digital systems, and adaptive organizational support.